2005
DOI: 10.1063/1.1850655
|View full text |Cite
|
Sign up to set email alerts
|

Noncontact determination of elastic moduli by two-dimensional Fourier transformation and laser ultrasonic technique

Abstract: Broadband laser ultrasonics and two dimensional Fourier transformation are used to characterize the properties of varieties of foils and plates. Laser ultrasonics generation is achieved by use of a pulsed laser which deposits pulsed laser energy on the surface of the specimen. The displacement amplitude of the resulting broadband ultrasonic modes are monitored using a two wave mixing photo-refractive interferometer. By applying a two dimensional Fourier transformation to the detected spatial and temporal displ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…They are classified as longitudinal or transverse characterized standing modes. 15,16,19 And their Fourier magnitudes are weaker than A0's and S0's in the 2DFT image. Figure 2͑b͒ illustrates the results for an aluminum plate with a square lattice of air-filled holes.…”
mentioning
confidence: 92%
See 3 more Smart Citations
“…They are classified as longitudinal or transverse characterized standing modes. 15,16,19 And their Fourier magnitudes are weaker than A0's and S0's in the 2DFT image. Figure 2͑b͒ illustrates the results for an aluminum plate with a square lattice of air-filled holes.…”
mentioning
confidence: 92%
“…The image displays the dispersion relations for the A0 ͑the lowest-order asymmetric Lamb mode͒, S0 ͑the lowest order symmetric Lamb mode, next to A0͒, and higher-order Lamb modes ͑the rest of the weak modes͒. 15,16,19 A0 mode has a large out-ofplane displacement component and hence is observed easily by the current laser ultrasonics setup. The S0 is an in-plane mode at low frequencies ͑below 1 MHz͒, however it becomes visible at high frequencies because its out-of-plane component increases with frequency.…”
mentioning
confidence: 96%
See 2 more Smart Citations
“…The laser generation of guided waves is usually performed by focusing the beam from a pulsed laser at the plate surface, so that broadband waves are generated, whereas the detection of guided wavetrains is usually performed by optical means, typically pointwise interferometers. [20][21][22][23][24] The applicability of the 2D FT method is not limited to plates. In fact, several authors have reported the use of this method to calculate the frequency spectrum of guided waves in other structures, for example, cylinders 25,26 or wedge tips.…”
Section: Introductionmentioning
confidence: 99%